2002
DOI: 10.1023/a:1014591020400
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fidelity scales have become an accepted part of intervention research. Initially, fidelity scales focused on critical components of an intervention. In this paper we argue that the next generation of fidelity scales should include key process variables such as choice. Since choice is an essential element in all empowerment and recovery driven intervention models, a fidelity scale for an enhanced version of the Individual Placement and Support (IPS) supported employment model that incorporates choice as a funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Other aspects of IPS implementation, which are not captured by the IPS fidelity scale, such as the nature of the relationship between the IPS worker and the client (which was an independent predictor of outcome in the EQOLISE study)26 may also explain the poorer outcomes found in this study. A recently developed modified IPS fidelity scale (IPS+) also includes rating essential processes such as consumer choice,27 and the IPS fidelity rating carried out in this study may have been lower if the IPS+ had been used.…”
Section: Discussionmentioning
confidence: 95%
“…Other aspects of IPS implementation, which are not captured by the IPS fidelity scale, such as the nature of the relationship between the IPS worker and the client (which was an independent predictor of outcome in the EQOLISE study)26 may also explain the poorer outcomes found in this study. A recently developed modified IPS fidelity scale (IPS+) also includes rating essential processes such as consumer choice,27 and the IPS fidelity rating carried out in this study may have been lower if the IPS+ had been used.…”
Section: Discussionmentioning
confidence: 95%
“…All 20 had at least four days of training in the EFIT model, and seven had at least 12 days of advanced training. The research literature varies in the number of expert raters used to develop a measure of adherence, with some studies using as few as two (Paulson et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…It is, therefore, common practice to use fidelity criteria to monitor fidelity of an intervention (Mowbray et al , 2003). Routine monitoring of programme delivery is also of great importance for ensuring consistency, particularly in multi-site studies (Paulson et al , 2002). In addition, fidelity measures can also serve as records of programme delivery to refer to, for example, when investigating why an intervention is ineffective (Chen and Chen, 1990; Hohmann and Katherine Shear, 2002; Mowbray et al , 2003).…”
Section: Introductionmentioning
confidence: 99%